Factors Influencing Purchase Decisions of Muslim Fashion In Banjarmasin (Case Study At Ve Fashion Banjarmasin) - Anggada Sakti Pamungkas; Eric Harianto (Dinasti International Journal of Education Management And Social Science, 2024)
The fashion industry is rapidly growing in Indonesia, particularly in Muslim fashion. By understanding the factors influencing purchasing decisions in Muslim fashion, businesses can plan more effective marketing strategies to remain competitive in a tough market. This research employs exploratory factor analysis to identify the factors considered in shaping purchasing decisions for Muslim fashion. The study utilizes primary data from respondents who have purchased Muslim fashion items in Banjarmasin, totaling 219 respondents. The findings reveal exploratory factor analysis using SPSS tools, identifying eigenvalues of two factors exceeding 1. The analysis indicates two primary factors influencing purchasing decisions: Quality of Service Information and Social and Economic Influence. Understanding these factors enables Ve Fashion to enhance customer satisfaction and influence purchasing decisions more effectively, thereby sustaining and expanding market share in the competitive Muslim fashion industry.